2005
DOI: 10.1086/427822
|View full text |Cite
|
Sign up to set email alerts
|

AChandraStudy of the Multicomponent X‐Ray Emission from the X‐shaped Radio Galaxy 3C 403

Abstract: We present results from a 49.4 ks Chandra/ACIS-S observation of the nearby (z=0.059) X-shaped FRII radio galaxy 3C 403. This is the first Chandra observation of an X-shaped radio galaxy, and one of the goals of this pioneering study is to determine the relationship between the X-ray emitting gas and the X-shaped radio morphology. We find that the X-ray isophotes of the hot gas within ∼3.5 ′′ of the central galaxy are highly elliptical (eccentricity∼0.57) and co-aligned with the elliptical optical isophotes. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 52 publications
(66 reference statements)
9
131
0
Order By: Relevance
“…The addition of a thermal Apec component did not significantly improve the fit ( 2 ¼ 29:0 for 48 dof, with the probability of achieving a greater F by chance of 18.4%). We compared the results of the spectral fitting to previously published Chandra data ( Kraft et al 2005) and found all parameter values to be consistent.…”
Section: A20 3c 403mentioning
confidence: 77%
See 1 more Smart Citation
“…The addition of a thermal Apec component did not significantly improve the fit ( 2 ¼ 29:0 for 48 dof, with the probability of achieving a greater F by chance of 18.4%). We compared the results of the spectral fitting to previously published Chandra data ( Kraft et al 2005) and found all parameter values to be consistent.…”
Section: A20 3c 403mentioning
confidence: 77%
“…In total, 16 Chandra and 5 XMM-Newton observations of the sources are available at the time of writing, with the majority taken from the public data archives, together with some proprietary GO and GTO data. We compare results with those for Centaurus A ), 3C 403 (Kraft et al 2005), and 3C 405 (Cygnus A). Centaurus A is the nearest and best studied AGN, while 3C 403 and 3C 405 are nearby FR II-type sources, and so each provides a useful comparison with the other sources in our sample.…”
Section: Observations and Analysismentioning
confidence: 99%
“…It would then be an obvious assumption that high-power jets are also able to accelerate such electrons. Indeed, some high-power jets show evidence for synchrotron X-ray emission (Sambruna et al 2004;Kraft et al 2005;Hardcastle & Croston 2005). Moreover, Stawarz & Ostrowski (2002), Rieger & Mannheim (2002), and Rieger & Duffy (2004) have all argued that efficient particle acceleration is possible in regions of velocity shear.…”
Section: Viability Of the Synchrotron Modelmentioning
confidence: 99%
“…Since the increase of the CMB energy density with redshift would cancel the surface brightness dimming with redshift, beamed IC-CMB X-ray jets at high redshift could be cosmic beacons that outshine their quasars (Schwartz 2002). Moreover, there are jets in FR II radio galaxies and quasars whose X-ray emission is either well explained as synchrotron emission on an extrapolation of the radio-optical spectrum (e.g., in some of the jets in the survey by Sambruna et al [2004], and in 3C 403 [ Kraft et al 2005]) or because the necessary Doppler factors cannot be achieved from geometrical considerations, such as in Pictor A (Hardcastle & Croston 2005), in which there is X-ray emission from the counterjet as well as the approaching jet. A detailed check of the beamed IC-CMB model is therefore warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Such emission has, however, been detected in several objects (e.g., 3C 303, 3C 15, Pictor A, or 3C 403; see Kataoka et al 2003a,b, Hardcastle & Croston 2005, and Kraft et al 2005. Obviously, detection of any X-ray counterjet would be of primary importance in this respect, since it would automatically exclude significant beaming, and thus impose very severe constraints on the jet emission models.…”
Section: Introductionmentioning
confidence: 99%